2018
DOI: 10.3390/su10082848
|View full text |Cite
|
Sign up to set email alerts
|

A Social Norms Intervention Going Wrong: Boomerang Effects from Descriptive Norms Information

Abstract: Abstract:A large body of research supports the idea of social norms communication promoting pro-social and pro-environmental behaviour. This paper investigates social norms communication in the field. Signs prompting consumers about sustainable seafood labels and informing them about other consumers' sustainable choices were displayed in supermarkets in Norway and Germany. Seafood sales (sustainably labelled versus unlabelled products) were observed before, during, and after the implementation of the signs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 66 publications
(94 reference statements)
4
78
1
Order By: Relevance
“…For example, using simple pro-ecological messages has been proven to be less effective when compared to using messages that refer to social norms (e.g., De Groot, Abrahamse, & 5 Jones, 2013;Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008). Overall, normative information is considered to be a highly-effective type of environmental appeal (Cialdini, 2003) typically implemented by signs (Richter, Thøgersen, & Klöckner, 2018), and therefore will be thoroughly addressed in the presented research.…”
Section: Prompting Conservative Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…For example, using simple pro-ecological messages has been proven to be less effective when compared to using messages that refer to social norms (e.g., De Groot, Abrahamse, & 5 Jones, 2013;Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008). Overall, normative information is considered to be a highly-effective type of environmental appeal (Cialdini, 2003) typically implemented by signs (Richter, Thøgersen, & Klöckner, 2018), and therefore will be thoroughly addressed in the presented research.…”
Section: Prompting Conservative Behaviormentioning
confidence: 98%
“…For example, watching someone throwing litter in a trash bin (positive descriptive norm-support cue) in an already littered setting (negative descriptive norm-support cue) may not restrain an individual from littering, in contrast to a similar situation in an environment where there is no litter (Reno, Cialdini & Kallgren, 1993). Moreover, descriptive norm cues that address the common occurrence of norm-violating behavior may lead to even higher rates of occurrence (boomerang effect; Richter et al, 2018;Winter 2006). However, people not only can be de-motivated by descriptive normconflict, but norm-conflict can encourage people to take action.…”
Section: The Influence Of Social Normsmentioning
confidence: 99%
“…The suppression effect in Study 2 was the first evidence that descriptive norms backfire even when the majority act in a desirable way. Richter et al (2018) found that the boomerang effect occurred when descriptive normative message stated that less than half of others performed the designated behavior; however, we showed that even descriptive norms in which more than half perform the behavior can induce adverse effects.…”
Section: Practical Implicationsmentioning
confidence: 49%
“…We investigated not only the promotive effect of descriptive norms but also the pitfalls of them, such as the boomerang effect (Richter, Thøgersen, & Klöckner, 2018;Schultz et al, 2007).…”
Section: Descriptive Norms Can Backfirementioning
confidence: 99%
“…The failings of a social norm manipulation could be interpreted in light of recent resea Richter, Thøgersen and Klöckner [63] who reliably replicated the appearance of a 'Boomera on the social norms manipulation in their study on sustainable consumption choice supermarket. This effect is when the target behaviour of the social norm manipulation resu increased uptake of the behaviour that one is seeking to reduce.…”
Section: Discussionmentioning
confidence: 99%